Complications of Morbid Obesity in the Treatment of Acetabular Fractures: Re-evaluating Outcomes a Decade Later. Issue 2 (February 2022) - Robertson, Michael J.; Lee, Rowdy C.; Bergin, Patrick F.; Graves, Matthew L.; Russell, George V.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Objectives: To determine the rate of perioperative complications between morbidly obese (body mass index greater than 40 kg/m 2 ) and nonmorbidly obese patients undergoing operative treatment of acetabular fractures across 2 periods (2000–2005 and 2012–2019). Design: Retrospective, case–control study. Setting: Level I academic trauma center. Patients: Four hundred thirty-five consecutive patients from 2000 to 2005 and 216 consecutive patients from 2012 to 2019 with acetabular fractures treated by a single surgeon. Intervention: Operative fixation of acetabular fracture. Main Outcome Measurements: Outcome variables include positioning time, operative time, estimated blood loss, hospital stay, wound complications, and perioperative complications. Results: Twenty-eight morbidly obese and 188 nonmorbidly obese patients from 2012 to 2019, as well as 41 morbidly obese patients and 394 nonmorbidly obese patients from 2000 to 2005 were included in the study. The relative risk (RR) of wound complications between 2012 and 2019 groups was significantly higher for morbidly obese patients (RR = 5.31, P = 0.009) but has decreased significantly for morbidly obese patients between 2000–2005 and 2012–2019 (RR = 0.31, P = 0.017). The rate of total perioperative complications was similar between morbidly obese and nonmorbidly obese groups from 2012 to 2019 (21% vs. 8%, P = 0.230). For morbidly obese patients, the rate of total perioperative complications decreased significantly between 2000–2005 and 2012–2019 (63% vs. 21% P = 0.010). Conclusion: Acetabular fracture surgery can be safely performed in morbidly obese patients. Although obesity remains a significant risk factor for wound complications, the risk for morbidly obese patients has decreased significantly since our initial investigation because of adaptations to surgical techniques and surgeon's experience. Level of Evidence: Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence.